The Influence of Price, Product Quality, and Service Quality on Customer Satisfaction of the President's Es Teh Franchise, Tembalang Branch in Semarang City - Grace Steefanie Roi (Escalate : Economics and Business Journal, 2026)
The increasingly competitive development of the contemporary tea-based beverage industry requires business actors to understand the factors that influence customer satisfaction. This study aims to analyze the influence of price, product quality, and service quality on customer satisfaction at the Es Teh Presiden franchise, Tembalang branch, Semarang City, both partially and simultaneously. The study used a quantitative approach with an associative causality design. The study population was all consumers of the Es Teh Presiden franchise, Tembalang branch, with an unknown population size, while a sample of 96 respondents was determined using the Lemeshow formula. Data were collected through a five-point Likert scale questionnaire, then analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficients of determination. The results showed that price and product quality had a positive and significant effect on customer satisfaction, while service quality did not have a significant effect partially. Simultaneously, price, product quality, and service quality had a significant effect on customer satisfaction with a coefficient of determination of 34.6%. In conclusion, customer satisfaction is more influenced by perceptions of price and product quality than service quality, so companies need to prioritize product quality consistency and competitive pricing to increase customer satisfaction